Biotechnology applications of tethered lipid bilayer membranes - Jackman, Joshua A. (2014)
The importance of cell membranes in biological systems has prompted the development of model membrane platforms that recapitulate fundamental aspects of membrane biology, especially the lipid bilayer environment. Tethered lipid bilayers represent one of the most promising classes of model membranes and are based on the immobilization of a planar lipid bilayer on a solid support that enables characterization by a wide range of surface-sensitive analytical techniques. Moreover, as the result of molecular engineering inspired by biology, tethered bilayers are increasingly able to mimic fundamental properties of natural cell membranes, including fluidity, electrical sealing and hosting transmembrane proteins. At the same time, new methods have been employed to improve the durability of tethered bilayers, with shelf-lives now reaching the order of weeks and months. Taken together, the capabilities of tethered lipid bilayers have opened the door to biotechnology applications in healthcare, environmental monitoring and energy storage. In this review, several examples of such applications are presented. Beyond the particulars of each example, the focus of this review is on the emerging design and characterization strategies that made these applications possible. By drawing connections between these strategies and promising research results, future opportunities for tethered lipid bilayers within the biotechnology field are discussed.